Assessment Of Risk As A Sustainable Coffee Supply Chain Strategyon Rural Area In Jember Regency - Prawitasari, Saptya; muliasari , Risa Martha (Universitas Muhammadiyah Jember, 2024)
Risk assessment is essential for effectively and efficiently evaluating and controlling risks to create a sustainable coffee supply chain. The goals of this research are to identify the factors that influence quality risk and risk mitigation in small-holder coffee. The ANP method is used to identify the cause of a problem in the smallholder coffee supply chain by taking into account the occurrence criteria (O), severity (S), and detection (D). Data is gathered through interviews with expert respondents and experts from farmers, cooperatives, agro-industries, researchers, and academics who have been involved in the coffee agro-industry for at least ten years. The analyses' findings reveal a structural model for identifying and prioritizing risks by identifying six factors and 16 sub-factors. According to the findings of this study, farmers' knowledge and skills in terms of cultivation techniques are the main risks of relative importance in the coffee supply chain and thus require attention. Mitigation efforts that can be taken include improvements to cultivation that focus on the management of pests and diseases of coffee plants, as well as technical education and training. Factors that prevent farmers from accessing and implementing training must be considered so that knowledge and skills can be effectively provided.